TRANSMISSION OF LARGE VOLUME OF ASTRONOMICAL DATA - Isaev, E. A.; Kornilov, V. V.; Samodurov, V. A.; Tarasov, P. A.; Tarasova, J. A. (Одеські астрономічні публікації, 2013)
This article shows an overview of the world’s major astronomical research programs, for work requiring high-speed data, in particular, examples of major domestic (PRAM ASC LPI) and foreign projects (ALMA, VLA, SDSS, LSST, HESS, MWA, ACT). At the moment the local network to cope with data obtained from experiments load, but for future projects and the development and modernization of operating projects to the emergence of new technological solutions, due to the increased flow experimental data.